Facial paroxysmal hemicrania associated with the menstrual cycle - Christian Ziegeler; Arne May (SAGE Publishing, 2019)
Paroxysmal hemicrania (PH) is a rare trigeminal autonomic cephalalgia (TAC) which is usually not associated with the menstrual cycle and usually affects the first trigeminal branch. We present a 47-year-old female patient with a facial variant of PH. For over 11 years, the patient had suffered from 8 to 12 typical PH attacks per day localized in the left maxilla in bouts of 4-9 days solely during her menstruation and ovulation. Single dosages of indomethacin 25 mg showed good efficacy in the prevention of the attacks for several hours. However, the intake of indomethacin had to be ceased due to severe psychiatric side effects. Ibuprofen 400 mg also reliably reduces the attack frequency with the same effectiveness as indomethacin. Attacks of PH can occur solely in the facial region and can be associated with the menstrual cycle which can prove to be a diagnostic challenge. Also, the intake of indomethacin can be limited by psychiatric side effects but can be adequately substituted by ibuprofen.